2022
DOI: 10.3390/md20030163
|View full text |Cite
|
Sign up to set email alerts
|

Neoechinulin A as a Promising SARS-CoV-2 Mpro Inhibitor: In Vitro and In Silico Study Showing the Ability of Simulations in Discerning Active from Inactive Enzyme Inhibitors

Abstract: The COVID-19 pandemic and its continuing emerging variants emphasize the need to discover appropriate treatment, where vaccines alone have failed to show complete protection against the new variants of the virus. Therefore, treatment of the infected cases is critical. This paper discusses the bio-guided isolation of three indole diketopiperazine alkaloids, neoechinulin A (1), echinulin (2), and eurocristatine (3), from the Red Sea-derived Aspergillus fumigatus MR2012. Neoechinulin A (1) exhibited a potent inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…As previously described, binding free energy estimation (∆G binding) and molecular dynamic simulations were performed [ 52 , 53 ]. The Supplementary Materials file has a detailed description of these procedures.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, binding free energy estimation (∆G binding) and molecular dynamic simulations were performed [ 52 , 53 ]. The Supplementary Materials file has a detailed description of these procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The in silico analysis revealed that the molecule aurasperone A targets M pro in SARS-CoV-2 [152]. Furthermore, neoechinulin A isolated from Aspergillus fumigatus MR2012 from the Red Sea exhibited an IC 50 value of 0.47 µM against SARS-CoV-2, with a similar target to M pro [153]. NeoB, an anti-HBV alkaloid isolated from A. amstelodami, also demonstrated anti-SARS-CoV-2 activity, inhibiting liver X receptors [20].…”
Section: Anti-sars-cov-2mentioning
confidence: 99%
“…M pro plays an essential role in the replication and transcription of SARS-CoV-2. There are a number of microbe-produced natural products with the ability to inhibit M pro , including aurasperone A [152]; neoechinulin A [153]; as well as aspulvinone D, M, and R [154].…”
Section: Possible Targetmentioning
confidence: 99%
“…Meanwhile, quercetin and caffeic acid were reported as 3CL protease inhibitors [ 13 ]. To accelerate the discovery of antiviral hits against SARS-CoV-2, molecular docking for thousands of known phyto-constituents was performed on the main protease by utilizing computer-aided programs [ 14 , 15 , 16 , 17 ]. The compounds with high activity in virtual screening encourage researchers to test them in vitro on SARS-CoV-2 M PRO .…”
Section: Introductionmentioning
confidence: 99%
“…The compounds with high activity in virtual screening encourage researchers to test them in vitro on SARS-CoV-2 M PRO . These studies afforded many active compounds against the main protease, such as neoechinulin A from Red-Sea-derived Aspergillus fumigatus MR2012 [ 16 ], naringenin [ 17 ], and cnicin from Carduus benedictus [ 18 ]. Moreover, thirty-eight African medicinal plants traditionally used as an antiviral and immunomodulator and for treating COVID-19 symptoms were reviewed previously to open the door for drug discovery from medicinal plants [ 19 ].…”
Section: Introductionmentioning
confidence: 99%